Substrate-specific pressure-dependence of microbial sulfate reduction in deep-sea cold seep sediments of the Japan Trench - Vossmeyer, Antje; Deusner, Christian; Kato, Chiaki; Inagaki, Fumio; Ferdelman, Timothy (Frontiers in Microbiology, 2012)
The influence of hydrostatic pressure on microbial sulfate reduction (SR) was studied using sediments obtained at cold seep sites from 5500 and 6200 m water depth of the Japan Trench. Sediment samples were stored under anoxic conditions for 17 months in slurries at 4˚ C and at in situ pressure (50 MPa), at atmospheric pressure (0.1 MPa), or under methanic conditions with a methane partial pressure of 0.2 MPa. Samples without methane amendment stored at in situ pressure retained higher levels of sulfate reducing activity than samples stored at 0.1 MPa. Piezophilic sulfate reduction showed distinct substrate specificity after hydrogen and acetate addition. SR activity in samples stored under methanic conditions was one order of magnitude higher than in non-amended samples. Methanic samples stored under low hydrostatic pressure and exhibed no increased SR activity at high pressure even with the amendment of methane. These new insights into the effects of pressure on substrate specific sulfate reducing activity in anaerobic environmental samples indicate that hydrostatic pressure must be considered to be a relevant parameter in ecological studies of anaerobic deep-sea microbial processes and long-term storage of environmental samples.